THE RELATIONSHIP BETWEEN pH VALUE OF IRON SUPPLEMENT WITH THE ABSORPTION OF IRON IONS IN DECIDUOUS TEETH (AN IN VITRO STUDY) - Ulfa Yasmin; Saphira Pramudita; Sulistiawati Sulistiawati; Novita Idayani (FKG ULM, 2025)
Background: Iron deficiency anemia is a prior health issue that often occurs in school-aged children. Iron substances have a critical role in neurological growth, so it is necessary to give iron supplements as therapy. Iron supplements can affect deciduous teeth. Aims: To measure the pH and absorption value of iron supplements in deciduous teeth and determine the relationship between pH value of iron supplements with the absorption of iron ions in deciduous teeth. Material and Methods: This study is an experimental in vitro- study. Sample groups used iron supplements (Ferriz, Sangobion Kids, Ferro-K). The assessment of pH value used pH meter, and iron ions absorption used Atomic Absorption Spectrometry. Spearman's Rank correlation test was used to analyze the correlation between iron supplements pH value and iron ions absorption in deciduous teeth. Results: The result showed that All iron supplements have acidic content, Sangobion Kids was a lower pH value, and Ferriz had a higher pH value. For the absorption iron ions value, the lowest was Sangobion Kids(0,5454),and the highest was Ferro-K (0,7979). Conclusion: pH value of iron supplements have a significant relationship with the absorption of iron ions in deciduous teeth and each pH value for Ferriz; Sangobion Kids; and Ferro-K are 6,0; 4,3; and 4,5 and the value of iron ions absorption in deciduous teeth are 0,5838; 0,5454; and 0,7979.